Eksploitasi hutan jati di Kabupaten Blora tahun 1845-1949 - Chilmi, Nazal; Ba'in, Ba'in (Journal of Indonesian History, 2020)
This study discusses the exploitation of teak forests in Blora Regency in 1945-1949. At the root of the problem are the different assumptions between the community and the government in teak forest policy. Land needs, wood resources owned by forests make production forest forests without considering the void of land and forest damage. The method in this study uses the historical method. Blora, which is one of the cities that has a large area of ​​teak forest, which has a large community with farmers. From the results of this study it can be concluded that the various problems caused by the war resulted in losses for the Indonesian government. The meaning of independence is often misunderstood by the village community so that there is an exploitation of teak forests to meet the needs of the community.